Graphene-Enabled Silver Nanoantenna Sensors - Reed, Jason C; Zhu, Hai; Zhu, Alexander Y; Li, Chen; Cubukcu, Ertugrul (Nano letters, 2012)
Silver is the ideal material for plasmonics because of its low loss at optical frequencies but is often replaced by a more lossy metal, gold. This is because of silver’s tendency to tarnish and roughen, forming Ag2S on its surface, dramatically diminishing optical properties and rendering it unreliable for applications. By passivating the surface of silver nanostructures with monolayer graphene, atmospheric sulfur containing compounds are unable to penetrate the graphene to degrade the surface of the silver. Preventing this sulfidation eliminates the increased material damping and scattering losses originating from the unintentional Ag2S layer. Because it is atomically thin, graphene does not interfere with the ability of localized surface plasmons to interact with the environment in sensing applications. Furthermore, after 30 days graphene-passivated silver (Ag–Gr) nanoantennas exhibit a 2600% higher sensitivity over that of bare Ag nanoantennas and 2 orders of magnitude improvement in peak width endurance. By employing graphene in this manner, the excellent optical properties and large spectral range of silver can be functionally utilized in a variety of nanoscale plasmonic devices and applications.